CHICKPEA MILK: NUTRITIONAL PROFILE, FUNCTIONAL CHARACTERISTICS, BIOACTIVE COMPOUNDS, AND QUALITY ENHANCEMENT – A COMPREHENSIVE REVIEW-: "Exploring Chickpea Milk: A Comprehensive Review" - HAMIOUD, Aya; BENMEZIANE, farida; DJERMOUNE-ARKOUB , lynda (Food and Feed Research, 2025)
The prevalence of cow’s milk allergies and lactose intolerance has been growing alongside the evolution of bovine milk consumption and production; consequently, the itching need for an alternative has been the subject of many studies and a growing trend in the milk industry. Plant-based milks have emerged as the most popular and suitable substitutes; they are beverages extracted from cereals, pseudo-cereals, legumes, nuts or seeds. Legumes, due to their high protein content have proven to be one of the successful options. One such legume is chickpea, which not only boasts rich protein content but also contains minerals, fibers, unsaturated fatty acids, bioactive compounds and antioxidant properties. Despite the limited studies available regarding the development of chickpea-based milk alternatives, this review draws upon insights from existing studies that have explored chickpea milk. It covers a range of topics, including the nutritional composition compared to other plant-based substitutes, the health benefits associated with bioactive and functional compounds, and the most novel methods employed in the extraction of non-dairy beverages.
Keywords: plant-based beverage; proteins; pulses; bioactive compounds; novel technologies; functional properties; shelf-life